Intraosseous noninvoluting congenital hemangioma of the mandible in a neonate - Mutlu, Mehmet; Yarış, Nilgün; Aslan, Yakup; Kul, Sibel; İmamoğlu, Mustafa and Ersöz, Şafak (The Turkish Journal of Pediatrics, 2009)
Hemangiomas are benign tumors of the capillary endothelium involved in varied clinical and pathologic entities. Congenital hemangioma is quite rare compared to infantile hemangioma. Hemangiomas rarely occur in bone. Intraosseous hemangiomas are most commonly found in the vertebral column and skull. The mandible is the most frequently affected skull bone. Intraosseous hemangiomas commonly present in the second decade of life. Here, we report a neonate with noninvoluting congenital hemangioma of the mandible. To our knowledge, she is the youngest patient reported in the literature.